Asuhan Kebidanan Komprerensif pada Ny. H Umur 36 Tahun dengan Presentasi Bokong di Puskesmas Kaliwadas Kabupaten Brebes Tahun 2023 - Yuliani Rizqi Amalia; Himatul Khoeroh; Sri Mulyani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Pregnancy with breech presentation is where the fetus lies longitudinally in the uterus while the head is at the fundus uteri and in the buttocks position below the uterine cavity (Putri and Ningrum, 2019). Cases of breech presentation both mother and fetus experience a large increase in risk and for labor with breech location have high mortality and morbidity (Putra 2015). The maternal mortality rate (MMR) according to WHO 2021 is 32.9/100,000 KH. ASEAN 2021 MMR is 235/100,000. Indonesian Ministry of Health 2021 AKI 7,389 people, Central Java Health Office 2023 AKI as much as 485. Data from the Brebes Health Office 2022 as many as 50 cases while from the kaliwadas puskesmas area in 2022 there was 1 case of death. Researchers implement comprehensive midwifery care using Varney and SOAP documentation. This study uses descriptive qualitative methods through direct approaches, interviews, observation and documentation. The main informant is Mrs.H while for additional informants there are village midwives, puskesmas midwives, husbands and Mrs.H's family. Based on the results of research obtained from the care of pregnancy, childbirth, postpartum, LBW and family planning, problems were found in the form of pregnancy with breech presentation and cesarean delivery for indications of failed induction.